Особливості і характеристика історичної житлової забудови - Демків, Мирон; Погранична, Ірина; Demkiv, Myron; Pohranychna, Iryna (Видавництво Львівської політехніки, 2022)
Статтю присвячено актуальним проблемам щодо вибору підходів із перепланування існуючих квартир, реконструкції історичної забудови Львова з надбудовою мансард, додаткових поверхів або без них. У сучасній міській забудові сьогодні існує значний фонд житлових будинків із попередніх історичних епох і стилів. Стан планування переважноï більшості будинків не узгоджується із сучасними санітарними, протипожежними та функціональними вимогами і не відповідають сучасним умовам проєктування. Такий стан вимагає фахової роботи спеціалістів, здатниx вирішувати зазначені проблеми.

The article is devoted to the current problems of housing reconstruction in Ukraine, as well as ways to solve them. The article highlights domestic and foreign experiences in the redevelopment of existing apartments and reconstruction of historical buildings with or without superstructure of attics or additional floors. In modern urban development today, there is a significant fund of residential buildings from previous historical eras and styles. The layout of the vast majority of houses does not meet modern sanitary, fire-fighting and functional requirements and does not meet modern design conditions. This situation requires the professional work of specialists who can solve these problems. In general, the reconstruction of historical residential development is aimed at: – an increase in the total area of apartments, which is achieved by combining existing apartments within a floor or by combining apartments on two floors; also an increase in apartments is possible due to the superstructure, extension or use of attics of the building; – an increase in the area of living rooms, toilets, bathrooms and combined bathrooms due to hallways, intra-apartment corridors, built-in storerooms and wardrobes; – improvement of the planning scheme of apartments with the elimination of such typical shortcomings in historical buildings: entrance to the apartment from the gallery, entrance to the apartment through the kitchen, entrance to the bathroom from the kitchen, small area of the kitchen, living room, etc., passageways in the apartment, lack of bathrooms in the apartment, insufficient insolation of the premises, etc. – installation of communications for low-mobility groups of the population (ramps, elevators, etc.).
Features and characteristics of historical housing
Keywords: перепланування; реконструкція; історична забудова; житловий фонд; багатоквартирний будинок; redevelopment; reconstruction; historical development; housing stock; apartment building; 721